-17x-6=7-9x

Simple and best practice solution for -17x-6=7-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17x-6=7-9x equation:


Simplifying
-17x + -6 = 7 + -9x

Reorder the terms:
-6 + -17x = 7 + -9x

Solving
-6 + -17x = 7 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-6 + -17x + 9x = 7 + -9x + 9x

Combine like terms: -17x + 9x = -8x
-6 + -8x = 7 + -9x + 9x

Combine like terms: -9x + 9x = 0
-6 + -8x = 7 + 0
-6 + -8x = 7

Add '6' to each side of the equation.
-6 + 6 + -8x = 7 + 6

Combine like terms: -6 + 6 = 0
0 + -8x = 7 + 6
-8x = 7 + 6

Combine like terms: 7 + 6 = 13
-8x = 13

Divide each side by '-8'.
x = -1.625

Simplifying
x = -1.625

See similar equations:

| 5x+4=24+x | | 3/5= | | 6y-7=-1 | | 9y=15+4y | | 3(y+2)=8y+10 | | -6+9x=6+8x | | -6-9x=6+8x | | -35+-2f+f^2=0 | | 7(8-z)=21 | | 2(2y-3)=4+3(y-2) | | 6y-7=41 | | 1(6a-6)=12(6a-6) | | 8(3x+2)=184 | | 6(9x+5)=246 | | 9x+8=-20+2x | | 8(5+y)=88 | | 6(5+z)=42 | | 7+3n=35 | | 9(2+y)=72 | | 3(4z+7)=45 | | (4n+3n)+(6n+2n)=30 | | 2(3y+5)=64 | | 2(x-1)=x+6 | | 4(8x+5)=212 | | 5x-2x=x+16 | | 3x+16=4x+5 | | 20=13-6 | | 5x-7y=2x+3 | | 4x^2-5x+13=3x+10 | | 5x+3y+8=0 | | 2y^2+5y-3=(2y-1) | | 2y^2+5y-3= |

Equations solver categories